2014
DOI: 10.1007/s11284-014-1232-4
|View full text |Cite
|
Sign up to set email alerts
|

Tree diameter structural diversity in Central European forests withAbies albaandFagus sylvatica: managed versus unmanaged forest stands

Abstract: The biodiversity of forest stands should be analysed from the point of view of not only compositional elements but also structural diversity. The main objective of this study was to compare tree diameter structural diversity of the mixed managed and unmanaged stands with Abies alba and Fagus sylvatica. There were 62 study plots established in the Carpathians (Southern Poland) and in the S´więtokrzyskie Mountains (Central Poland) in managed and unmanaged stands. The comparison of the studied stands involved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 82 publications
4
23
1
Order By: Relevance
“…In addition to the diversity in tree species, structural diversitycharacterized as the heterogeneity in vertical and horizontal structures (Pach & Podlaski 2014)is another important dimension of diversity in forest ecosystems (Moser & Hansen 2006). Also structural diversity has been reported to promote forest productivity (Hardiman et al 2011;Fahey et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the diversity in tree species, structural diversitycharacterized as the heterogeneity in vertical and horizontal structures (Pach & Podlaski 2014)is another important dimension of diversity in forest ecosystems (Moser & Hansen 2006). Also structural diversity has been reported to promote forest productivity (Hardiman et al 2011;Fahey et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in accordance with Fahlvik et al (2015), who reported a significant influence of the structure of mixed stands (Scots pine, Norway spruce and birch in Sweden) during pre-commercial thinning. On the other hand, Pach and Podlaski (2015) found that unmanaged mixed fir/beech stands showed more complex diameter structural diversity compared to managed mixtures. In our study, the above-mentioned trends need (dis)confirmation by subsequent research based on wider experimental material, because of non-replicated plots and relatively small initial proportion of beech in Deštné experiment (especially control plot).…”
Section: Discussionmentioning
confidence: 94%
“…Boncina 2011), most studies focus on boreal forests or on the beech and spruce forest zone (Dieler et al 2017). Such forests contain fewer large old trees and less deadwood than primeval forests (Motta et al 2014;Pach and Podlaski 2015), while they can be richer in large trees, gaps, and patches of natural regeneration than rotation forests and recently abandoned rotation forests (Dieler et al 2017;Keren et al 2017;Mölder et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%